Bilateral adrenal giant medullary lipoma combined with disorders of sex development: a rare case report and literature review - Zhanghuang, Chenghao; Long, Na; Yang, Zhen; Xie, Yucheng (Frontiers in Oncology, 2023)
Bilateral adrenal myelolipoma is rare in clinics and patients with disorders of sex development (DSD). One case was reported in our center. A 45-year-old patient was admitted to the hospital after discovering a left abdominal mass for more than a year and worsening abdominal pain for 18 days. An imaging examination showed bilateral adrenal masses. Physical examination showed clitoris hypertrophy with patelliform changes, thick and dense pubic hair, normal development of bilateral labia majora without labia minora, and urethral opening. After the relevant preoperative examinations, bilateral adrenal mass resection was performed under general anesthesia. The postoperative pathology confirmed adrenal myelolipoma. The incision healed well without recurrence over ten years after the operation. Her enlarged clitoris decreased in size. This case report has a detailed diagnosis and treatment process and sufficient examination results. It can provide a reference for diagnosing and treating patients with bilateral adrenal myelolipoma and DSD and reduce the risk of misdiagnosis and mistreatment.